Copper/copper oxide nanoparticles synthesis using Stachys lavandulifolia and its antibacterial activity. Issue 6 (25th July 2017) - Khatami, Mehrdad; Heli, Hossein; Mohammadzadeh Jahani, Peyman; Azizi, Hakim; Lima Nobre, Marcos Augusto
Abstract : Nanoparticles of copper/cuprous oxide (Cu/Cu2 O) were successfully synthesised by a green chemistry route. The synthesis process was carried out using an extract of Stachys lavandulifolia as both reducing and capping agents with a facile procedure. The nanoparticles were characterised by different techniques including X‐ray diffraction, indicating that the synthesised sample comprised both copper and cuprous oxide entity. The nanoparticles had a mean size of 80 nm and represented an impressive bactericidal effect on Pseudomonas aeruginosa .